6 Variation in practice in endometrial cancer (EC); can molecular classification direct care and reduce costs associated with management?. (13th November 2020) - Thompson, E; Lum, A; Huvila, J; Scott, S; Lui, V; He, E; Salisbury, T; Keane, S; Keane, S; Samouelian, V; Irving, J; Salvador, S; et al.
Abstract : Objectives: We wished to assess the potential impact of directing EC management based on molecular classification, and the projected cost implications of molecular subtype-directed care. Methods: Surgical staging, treatment, surveillance, and hereditary cancer program(HCP) referrals were assessed for all ECs managed in a single calendar year (2016) across 24 Canadian centers. Variation of practice was recorded, as well as where a change in management would be projected and associated cost implications of that change based on molecular subtype assignment. Results: Data from 862 patients revealed wide variation in surgical staging, with lymph node dissection(LND) performed in 61% of ECs (range 25–100%), including 38% LND in Gr1ECs (0–100%). Adjuvant therapy (type, when/if given) and cancer surveillance (frequency, site e.g., community vs. cancer center) was inconsistent within and across centers for both early-and late-stage disease. Molecular classification identified 29% MMRd ECs (n=247) but only 8% of these women had been referred to HCP. 30 women who did consult HCP were MMRproficient. 38% of MMRd ECs had no LND and 43% did not receive radiation. 16% and 18% of p53abn ECs had no LND or omentectomy respectively, and only 58% received chemotherapy. De-escalation of treatment in early-stage POLEmut and NSMP ECs (n=63 treated, where molecular classification would direct observation or brachytherapy-only) would have reduced costs by 348, 896–407, 830CAD or 5538–6466CAD per patient. Conclusions: There is currently profound variation in practice for all aspects of EC management with implications to patients and health systems. Molecular classification can provide consistency in care and direct biologically-informed management.